ON ?- STATISTICAL CONVERGENCE OF ORDER a IN PROBABILITY - Isik, Mahmut; Akbas, Kubra Elif (Univ Prishtines, 2017)
In this study we introduce and examine the concepts of lambda-statistical convergence of order a in probability and strong (V, lambda) summability of order a in probability.
Keywords: Statistical convergence of order a in probability; Cesaro summability of order a in probability